VDIDAL: ASSESSMENT, TASTE AND THERAPY - Thakare, Manisha Sanjay; Thakare, Komal (ShodhKosh: Journal of Visual and Performing Arts, 2023)
'Social awareness' is an important feature of science literature. In order to bring the society out of the traditional yoke, which was mired in undesirable practices and traditions, it was necessary to adopt scientific thinking. Science is special knowledge. Science is development. Literature reflects the real society. Literary science dates back to the development at the beginning of creation. Science creates a vision of reality. Bal Fondake's story. His collection of stories, Vdidal, certainly depicts how humans and their interactions will be in the future.